ANALYSIS OF CLASS 1 MERDEKA CURRICULUM TEACHING MODULES AT XAVERIUS 1 PRIMARY SCHOOL PALEMBANG - Lestari, Fitria; Triayomi, Ria (IJBLE Scientific Publications Community Inc., 2023)
The current education system in Indonesia has implemented a new curriculum known as the Merdeka Curriculum. Merdeka Curriculum is a refinement curriculum from the 2013 Curriculum. In the implementation of Merdeka Curriculum, it consists of teaching modules used in the learning process. The Ministry of Education, Culture, Research and Technology explained that the Merdeka Curriculum focuses on essential content and the development of students' competencies in each phase to enable students to learn more deeply, meaningfully, and enjoyably. The objective of this research is to describe the analysis results of the teaching modules in Merdeka Curriculum in Xaverius 1 Primary School Palembang. In accordance with the teaching modules based on the decision of the Ministry of Education and Culture, Research and Technology No 033/H/KR/2022. This research used a qualitative descriptive approach method. The technique of collecting data involves interviews, questionnaires, and documentation. The subject in this research is Parallel Teacher in 1A, 1B, 1C, 1D Classes and the research object is the teaching modules for grade 1. Data validity is ensured through source triangulation. The technique of analyzing data used an interactive model from Miles Huberman. The result of this research indicated 91.1% compliance with teaching modules, syllabi, and ATP (Annual Program Plans), with 8.88% non-compliance. Meanwhile, the compliance of components and alignment with Learning Objectives within the elements is 100%.